Emerging drugs for the treatment of neuromyelitis optica. (2nd July 2020) - Duchow, Ankelien; Chien, Claudia; Paul, Friedemann; Bellmann-Strobl, Judith
ABSTRACT: Introduction: Evidence-based treatment options for neuromyelitis optica spectrum disorders (NMOSD) patients are beginning to enter the market. Where previously, there was only the exclusive use of empiric and off-label immunosuppressants in this rare and devastating central nervous system autoimmune disease. Areas covered: In accordance to expanding pathogenetic insights, drugs in phase II and III clinical trials are presented in the context of the current treatment situation for acute attacks and immunopreventative strategies in NMOSD. Some such drugs are the 2019-approved complement inhibitor eculizumab, other compounds in late development include its modified successor ravulizumab, IL-6 receptor antibody satralizumab, CD19 targeting antibody inebilizumab and the TACI-Fc fusion protein telitacicept. Expert opinion: Moving from broad immunosuppression to tailored treatment strategies, the prospects for efficient NMOSD therapy are positive. For the first time in this disease, class I treatment evidence is available, but long-term data will be necessary to confirm the overall promising study results of the compounds close to approval. While drug development still centers around AQP4 antibody seropositive patients, current and future research requires consideration of possible diverging treatment demands for the smaller group of seronegative patients and patients with presence of MOG antibodies.